Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Tenaga Kerja pada PT. Cipta Mandiri Logistik - Sopian, Adhe Oktapiani; Isyanto, Puji (LANCAH: Jurnal Inovasi dan Tren, 2024)
The aim of this research is to determine the effect of occupational safety and health on workforce productivity at PT. Cipta Mandiri Logistik. In the industrial world, occupational safety and health are important factors for the workforce. The method used is quantitative. Data collection was carried out by creating questionnaire questions which were given to workers within PT. Cipta Mandiri Logistik. The collected data will then be processed using SPSS and data testing will be carried out using the normality test, simple linear regression equation, validity test, coefficient test and partial test (T test). The research results show that at PT. Cipta Mandiri Logistik, occupational safety and health have a positive and significant effect on workforce productivity.